21. KAJIAN HISTOKIMIA SEBARAN KARBOHIDRAT PADA KELENJAR MANDIBULARIS DAN KELENJAR LINGUALIS AYAM PETELUR (Gallus sp.) Histochemical Study of Mandibular and Lingual Glands Carbohydrate Distribution in Layer (Gallus sp.) - Hamny H (Universitas Syiah Kuala, 2016)
The objective of this study was to investigate the distribution of carbohydrate in the mandibular and lingual glands of layer in difference age groups histochemically.The study was observed the mandibular and lingual glands from nine layers which grouped into three groups namely starter aged 40 days old, productive aged seven months old, and post-productive aged 1.5 years old. Each group consisted of three layers. A small piece of mandibular and lingual glands were fixed in Bouin solution for subsequent processed into histological preparation.The distribution of carbohydrate in both of glands detected by alcian blue staining (AB) pH 2.5 and periodic acid schiff (PAS). The result showed that mandibular and lingual glands of the three group layers reacted positively to AB pH 2.5 and PAS which found in the cytoplasm of cell and in the secretion on lumen. In the cytoplasm, the mandibular and lingualis reacted positively to AB pH 2.5 and PAS with the intensity ranging from weak reaction(+) to strong (+++), while in the lumen of glands showed negative reaction (-) to positive with the intensity of weak (+) to strong (+++). In mandibular gland, the acid carbohydrates were found with strong intensity (+++) in the productive and post-productive layer, while neutral carbohydrates were found with the same intensity on starter, productive and post-productive layers. In the lingual gland, the acid carbohydrates found with strong intensity in the three groups of layers while the neutral were found with strong intensity (+++) in the starter and post-productive layer. Positive reaction to AB pH 2.5 and PAS indicated that both of the salivary glands contain the neutral and acid carbohydrate. ____________________________________________________________________________________________________________________ Key words: mandibular gland, lingual gland, acid carbohydrate, neutral carbohydrate, layer